Nonmesh laparoscopic repair of incarcerated obturator hernia - Ching-Ching Chen; Ting-Yuan Feng; Ren-Tzer Wang; Hao-Ming Chang (Journal of Medical Sciences, 2023)
Obturator hernia (OH) is uncommon. With its low incidence, diagnosis can be difficult with physical exams and laboratory data only. Imaging study with computer tomography significantly improved diagnosis accuracy and lower bowel resection and mortality rate. We present a rare case of a 70-year-old female with OH and managed by laparoscopic nonmesh repair method.